High‐Speed Roll‐to‐Roll Hot Embossing of Micrometer and Sub Micrometer Structures Using Seamless Direct Laser Interference Patterning Treated Sleeves1 . Issue 11 (22nd May 2017) - Rank, Andreas; Lang, Valentin; Lasagni, Andrés Fabián
Abstract : In this study, we present a seamless high‐speed roll‐to‐roll hot embossing process using a direct laser interference patterned nickel sleeve as a mold. Line‐like patterns with spatial periods of 5.0, 3.9, and 1.5 μm and structure heights of 572, 325, and 141 nm, respectively are used for imprinting PET‐foils. The influence of the web speed on the cavity filling and consequently on the structure height and homogeneity of the fabricated patterns is studied. The web speed is varied between 2 and 50 m min −1 . For the 5.0 and 3.9 μm periods, a decrease in structure height with the web speed occurs, while for the 1.5 μm period the structure height remains constant in the tested interval. Also a decrease in homogeneity is observed with increasing web speed. Finally, an analytical model, based on the Navier–Stokes equation and Hertzian contact pressure, is used to explain the experimental results. The experimental data are in good agreement with the calculated theoretical values. Abstract : A seamless high‐speed Roll‐to‐Roll hot embossing process using a direct laser interference patterned Nickel sleeve as a mold is presented. Line‐like periodic patterns with spatial periods of 5.0, 3.9, and 1.5 µm are fabricated directly on metallic sleeves using a two‐beam configuration interference set‐up. The influence of the web speed on the cavity filling and consequently on the structure height of the patterns produced on the PET foils is analyzed, for web speeds between 2 and 50 m min –1 . An analytical model, based on the Navier–Stokes equation and Hertzian contact pressure, is used to explain the experimental results.